Using Islamic Songs and Its Effect in Teaching English at an Indonesian Islamic University - Vinna Naralita; Yek Amin Azis (Universitas Islam Negeri (UIN) Mataram, 2020)
Islamic songs have gained prominence in the sphere of global education. However, they have yet received significant position in terms of the music scene, and little empirical evidence has been documented related to their use in Islamic universities or schools in Indonesia. Hence, this study aimed to fill this void and to investigate the effects of utilizing Islamic songs in teaching English at an Indonesian Islamic university. Grounded in a mixed-method case study, this study collected the data by distributing a questionnaire to 100 students and 10 lecturers from an Islamic University in Metro, Indonesia. The major findings show that the use of Islamic songs gave positive effects on the students’ comprehension, motivation and class atmosphere. The incorporation of the Islamic songs in the teaching of English could enrich the students’ knowledge of Islamic vocabulary.